The Molecular Basis of Spinocerebellar Ataxia Type 7 - Goswami, Rituparna; Bello, Abudu I.; Bean, Joe; Costanzo, Kara M.; Omer, Bwaar; Cornelio-Parra, Dayanne; Odah, Revan; Ahluwalia, Amit; Allan, Shefaa K.; Nguyen, Nghi; Shores, Taylor; Aziz, N. Ahmad; et al. (Frontiers in neuroscience, 2022)
Spinocerebellar ataxia (SCA) type 7 (SCA7) is caused by a CAG trinucleotide repeat expansion in the ataxin 7 ( ATXN7 ) gene, which results in polyglutamine expansion at the amino terminus of the ATXN7 protein. Although ATXN7 is expressed widely, the best characterized symptoms of SCA7 are remarkably tissue specific, including blindness and degeneration of the brain and spinal cord. While it is well established that ATXN7 functions as a subunit of the Spt Ada Gcn5 acetyltransferase (SAGA) chromatin modifying complex, the mechanisms underlying SCA7 remain elusive. Here, we review the symptoms of SCA7 and examine functions of ATXN7 that may provide further insights into its pathogenesis. We also examine phenotypes associated with polyglutamine expanded ATXN7 that are not considered symptoms of SCA7.